Partial Restoration of Normal Functional Properties in Carboxypeptidase A-Digested Hemoglobin - Bonaventura, Joseph (1972)
In the absence of organic phosphates human hemoglobin A digested with carboxypeptidase A (des His, Tyr β) has high ligand affinity, a greatly reduced Bohr effect, and no heme-heme interaction. Under these conditions, it shows the simple, homogeneous ligand-binding kinetics characteristic of noncooperative heme proteins in which the high combination velocity for both O(2) and CO accounts, to a larger extent, for the increased affinity for both these ligands. Addition of inositol hexaphosphate dramatically alters the functional properties of this digested hemoglobin. The Bohr effect is greatly increased, and at neutral pH the protein shows significant, though still reduced, heme-heme interaction, together with a 5-fold decrease in affinity. In the presence of saturating amounts of the organic phosphate, the value of n is pH dependent, dropping from 1.9 at pH 5.8 to 1.3 at pH 8.6. After inositol hexaphosphate addition, the combination of the deoxy form of the digested hemoglobin with CO is 10-times slower than that observed in the absence of the inorganic phosphate; also the combination with CO after flash photolysis is biphasic and is similar, in many respects, to that observed for unmodified hemoglobin. Besides these functional changes, addition of inositol hexaphosphate to the modified deoxyhemoglobin results in an increase in the extinction coefficient at 430 nm similar to that observed on mixing the isolated α and β chains of normal hemoglobin. The results are consistent with the idea that inositol hexaphosphate shifts an equilibrium between high- and low-affinity forms of the protein.